Allies and enemies : how the world depends on bacteria - Maczulak, Anne E. [ (Anne Elizabeth)] , 1954- (FT Press, 2011)
Bacteria: they are invisible, mysterious, deadly, self-sufficient and absolutely essential for all life. The author, a microbiologist who has hunted and worked with an extraordinary array of bacteria, offers a powerful new perspective on Earth's oldest creatures. They are the Earth's bacteria, and they have been here for four billion years. They are our partners, like it or not, even though some of them will happily kill us. This book tells the story of this amazing, intimate partnership